Genetic Purity Analysis of Maize (Zea mays L.) Hybrid Seed and Their Parents Produced in Different Seed Companies of Ethiopia - Gemechu Asefa Alemu; Elsabet Bayisa; Berhanu Tadesse; Adefiris Teklewold; Gowda Mange (Agro Bali : Agricultural Journal, 2022)
Genetic purity is one of the quality criteria required for successful seed production of maize. In hybrid seed production, genetic purity is contaminated due to out-crossing from other varieties or selfing events. In this study, Single nucleotide Polymorphisms (SNP) and Grow-out test (GOT) method was used for the objective to assess genetic purity of maize hybrid varieties with their parents produced by various seed growers in the country. Six three way cross hybrid (3WCH) maize varieties and seven single crosses were collected from different sources then planted with their parents in 2019. Genetic purity analysis by SNP revealed that 74% of an inbred line showed an acceptable genetic purity level (>95%). However, five inbred lines (CML395, A7033, F7215, SC22 and 124-b(113)) revealed heterogeneity >0.05 ranged from 0.13 to 0.20. All single crosses except A7033/F7215 and all the 3WCH varieties showed the genetic purity level ranging from 40 to 66% and 44 to 63% across seed sources, respectively. Based on GOT results, the level of type in single crosses and 3WCH variety across seed sources ranged from 7.1 to 46.4% and 3.6 to 35.7%, respectively. Generally, in the current result both SNP and GOT showed both heterogeneity and homogeneity of seed. This implies the presence of variation among seed producers in terms of producing high quality seed. Therefore, awareness should have to be given for each individual seed producers on quality seed production techniques and procedures that they have to follow. Similarly, genetic purity analysis could be conducted further in the seed system to provide error correction and to ensure seed quality assurance and control.